Single- vs multiple-layer wound closure for flank incisions: results of a prospective, randomised, double-blinded multicentre study - Kriegmair, Maximilian; Younsi, Nina; Hiller, Kiriaki; Leitsmann, Conrad; Kowalewski, Karl-Friedrich; Siegel, Fabian; Rothamel, Martin; Ritter, Manuel; Bolenz, Christian; Kriegmair, Martin; Trojan, Lutz; Michel, Maurice Stephan (BJU international, 2021)
Objective To compare the incidence of postoperative flank bulges between patients with multiple-layer closure and single superficial-layer closure after retroperitoneal surgery via open flank incision in the SIngle versus MUltiple-LAyer wound Closure for flank incision (SIMULAC) trial. Patients and Methods The study was a randomised controlled, patient- and assessor-blinded, multicentre trial. Between May 2015 and February 2017, 225 patients undergoing flank incisions were randomised 1:1 to a multiple-layer closure (SIMULAC-I) or a single superficial-layer closure (SIMULAC-II) group. The primary outcome was the occurrence of a flank bulge 6 months after surgery. Results Overall, 177 patients (90 in SIMULAC-I, 87 in SIMULAC-II) were eligible for final assessment. The cumulative incidence of a flank bulge was significantly higher in the SIMULAC-II group (51.7%) compared to the SIMULAC-I group [34.4%; odds ratio (OR) 2.04, 95% confidence interval (CI) 1.11-3.73; P = 0.02]. Rate of severe postoperative complications (4.4% SIMULAC-I vs 10.3% SIMULAC-II; P = 0.21) or hernia (6.7% SIMULAC-I vs 10.3% SIMULAC-II; P = 0.59) was similar between the groups. There was no difference in pain (visual analogue scale) and the requirement for pain medication at 6 months postoperatively. Quality of life assessed with the European Quality of Life 5 Dimensions Questionnaire was higher in the SIMULAC-I group compared to the SIMULAC-II group at 6 months postoperatively, with a (median range) score of 80 (30-100) vs 75 (5-100) (P = 0.012). Conclusion The overall risk of a flank bulge after flank incision is high. Multiple-layer closure after flank incision should be performed as a standard procedure.
First published: 21 June 2020
Gesehen am 18.05.2021